Digitalisasi Rumah Batu Kampung Al-Munawar di Palembang - Ramandika, Bagus; Alief, M. Arofandi; Iskandar, Iskandar (Jurnal TekstuReka, 2024)
This study examines the Stone House in the Arab village of Al-Munawar founded by Abdurrahman Al-munawar. The house has been inhabited by seven to eight generations, and its age is estimated to be between 200 and 300 years. By providing digital information about Al-Munawar Village, in particular Stone House, the researchers wanted to deepen their understanding of the history and structure of Stone House in al-Minawar Village. The research used literature studies to gather primary and secondary data. The data processing results were presented qualitatively and descriptively and discussed information about al-munawar village, especially Stone House. Researchers conducted direct surveys and measurements in Stone House to ensure the accuracy of the data. It produces digitized images that are accurate and suitable for field conditions.